COMPARISON OF EXFOLIATIVE CYTOLOGY AND INCISIONAL BIOPSY HISTOPATHOLOGY DIAGNOSING ORAL LEUKOPLAKIA’S IN SINDH HYDERABAD, PAKISTAN - Iqbal, Waqas; Arhama Surwaich; , Surwaich Ali Channa; , Abid Hussain Chang (Journal of University Medical & Dental College, 2020)
BACKGROUND & OBJECTIVES: The malignant neoplasms especially oral leukoplakia’s are recognized as a complex tumor with unique morphology. Current study aims to evaluate 182 clinically confirmed cases of oral leukoplakia with complete demographics. Where the major study objectives include; assessment of comparative sensitivity and specificity of exfoliative cytology diagnosing pre-malignant lesions. METHODOLOGY: Current cross-sectional, comparative histopathological study was carried out at Department of Dentistry - Isra Dental College, Isra University, and Liaquat University Hospital Hyderabad. About 182 cases of oral leukoplakia and 87 control healthy participants were enrolled in the study for exfoliative and incisional biopsy examination. RESULTS: The subjects were categorized into Group-I (182) patients and in group-II (87) healthy subjects. Males were at greater risk of oral leukoplakia (72.5%) as compared to females (27.5 %). Age group 31-40y with smoking history were more prone to oral leukoplakia’s (30.2%). where buccal mucosa and tongue-based site-specific leukoplakia lesions were common in group-I patients. From Group-I about 37.5 % cases of oral leukoplakia were identified as mild dysplasia and only six (3.3%) cases were severe dysplasia and 28.5 % cases were negative for AgNOR staining. The sensitivity analysis revealed 71.4% sensitivity of exfoliative cytology. CONCLUSIONS: Current two hospital-based study specifically focusing clinically confirmed oral leukoplakia cases suggest exfoliative cytology 71% sensitive and 93 % specific in routine settings. Where in advanced settings the outcomes may be more promising.